Novel gene signature reveals prognostic model in acute lymphoblastic leukemia - Chen, Panpan; Gao, Guanfei; Xu, Yuanlin; Jia, Peijun; Li, Yan; Li, Yating; Cao, Jiaming; Du, Jiangfeng; Zhang, Shijie; Zhang, Jingxin (Frontiers in Cell and Developmental Biology, 2022)
Acute lymphoblastic leukemia (ALL) is a malignant disease of abnormal proliferation of lymphocytes in bone marrow and has a poor prognosis. In our study, we aimed to identify the significant genes closely related to ALL and construct a prognostic model for predicting the prognosis of ALL. We obtained RNA-seq data of ALL samples from the GDC TARGET database. Differentially expressed genes (DEGs) were identified using the “DESeq” package of R software. Univariate and multivariate cox regression analyses were used to screen out the prognostic genes of ALL. Cox regression analyses results showed that the risk score was an independent prognostic factor [hazard ratio (HR) = 2.782, 95% CI = 1.903–4.068, P < 0.001]. The area under curve (AUC) for the risk score was 0.864 in receiver operating characteristic (ROC) analysis. Our study evaluated a potential prognostic signature with six genes and constructed a risk model significantly related to the prognosis of ALL patients. Findings from this study may help clinicians adjust treatment plans in a timely manner to differentiate patients with good and poor prognosis for targeted treatment.